2020
DOI: 10.3390/antiox9090890
|View full text |Cite
|
Sign up to set email alerts
|

Microparticles-Mediated Vascular Inflammation and its Amelioration by Antioxidant Activity of Baicalin

Abstract: Microparticles (MPs) are extracellular vesicles (0.1–1.0 μm in size), released in response to cell activation or apoptosis. Endothelial microparticles (EC-MP), vascular smooth muscle cell microparticles (VSMC-MP), and macrophage microparticles (MØ-MP) are key hallmarks of atherosclerosis progression. In our current study, we investigated the potent antioxidant activity of baicalin to ameliorate MP-induced vascular smooth muscle cell (VSMC) dysfunction and endothelial cell (EC) dysfunction, as well as the produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…When administered in vivo to a mouse MI model, these EVs preserved ventricular function and angiogenesis and decreased the degree of fibrosis in the infarct area [ 227 ]. In a study of vascular inflammatory mediators, EVs from LPS-treated endothelial cells stimulated endothelial dysfunction as shown by increased production of ICAM protein, ROS, and onset of cellular senescence but decreased levels of phospho-endothelial nitric oxide synthase and pAKT, while EVs from vascular smooth muscle cells produced increased levels of anti-fibrotic MMP-9 [ 228 ].…”
Section: Cardiac Fibrosismentioning
confidence: 99%
“…When administered in vivo to a mouse MI model, these EVs preserved ventricular function and angiogenesis and decreased the degree of fibrosis in the infarct area [ 227 ]. In a study of vascular inflammatory mediators, EVs from LPS-treated endothelial cells stimulated endothelial dysfunction as shown by increased production of ICAM protein, ROS, and onset of cellular senescence but decreased levels of phospho-endothelial nitric oxide synthase and pAKT, while EVs from vascular smooth muscle cells produced increased levels of anti-fibrotic MMP-9 [ 228 ].…”
Section: Cardiac Fibrosismentioning
confidence: 99%
“…Another key factor in lung cancer progression is the significance of matrix metalloproteinases (MMPs). MMPs are proteolytic enzymes which degrade various extracellular matrix (ECM) components (Paudel & Kim, 2020). One of the major MMPs involved in lung cancer is the MMP‐9.…”
Section: Introductionmentioning
confidence: 99%
“…MMPs are proteolytic enzymes which degrade various extracellular matrix (ECM) components (Paudel & Kim, 2020). One of the major MMPs involved in lung cancer is the MMP-9.…”
Section: Introductionmentioning
confidence: 99%
“…Baicalin (7-glucuronic acid-5,6-dihydroxy-flavone), is one of the primary bioactive flavonoid compounds extracted from the roots of Scutellaria baicalensis Georgi. Baicalin is used clinically in humans and animals because of its antimicrobial, anti-inflammatory, antitumor and antioxidant properties [ 21 , 22 , 23 , 24 ]. Our previously work demonstrated that baicalin has anti–inflammatory effects in G. parasuis -challenged piglets in vivo and in vitro by suppressing inflammatory cytokines and HMGB1 via NF-κB and NLRP3 signaling and reversing apoptosis by altering PKC–MAPK signaling cells [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%